Clinical Psychopathology During Covid-19 Pandemic - Thapa, Arati (Journal of College of Medical Sciences-Nepal, 2023)
The coronavirus disease 2019 (COVID-2019) pandemic and its consequences on individuals’ social, economic, and familial lives have negatively affected mental health of the general population especially in a vulnerable individual. In this case reports, we aim to highlight the role of such psychosocial stressors related to COVID pandemic resulting in development of Acute Psychosis. In the first case the stressor is associated with fear of getting infected while in the second case fear of being put into Quarantine. Thus health measures should be employed to address psychosocial stressors, particularly related to the use of isolation/quarantine, infection fear and vulnerability among the general population.